El nicho ecológico de los hominidos del Pleistoceno Medio de Atapuerca. - Bermudez de Castro Risueño, José María; Díez Fernández- Lomana, J. C.; Mosquera Martínez, Marina; Nicolás Checa, M. Elena; Pérez Pérez, Alejandro; Rodríguez Méndez, Jesús; Sánchez Marco, ANTONIO (Complutum, 1995)
Sin resumen